SISTEM INFORMASI E-LEARNING UNTUK PENGEMBANGAN MEDIA PEMBELAJARAN PADA MADRASAH ALIYAH - Dwi Retnosari; Muhammad Rais Wathani; Andie Andie (Universitas Lambung Mangkurat, 2017)
The long-term goal of this research is to participate in promoting the use of information and communication technology / Information Technology / Communications (ICT) in education. While the target is to create a good E-learning information system, with an attractive interface, simple and simple but can be understood easily by all users, both teachers and students as a media-based learning information and communication technology. This system is made with World Wide Web Consortium (W3C) Standardization which is a worldwide standard. By designing systems that comply with this standardization or obtain validation from the W3C, the system can be accessed by using various versions of different browsers and devices (responsive templates).